Near-real-time evaluation of the evolution of a seismic excitation: Application to the January 8, 2013 Lemnos seismic sequence. - Teza, E.; Scordilis, E. M.; Papazachos, C. B.; Karakaisis, G. F. (Bulletin of the Geological Society of Greece, 2013)
Monitoring the evolution of a seismic excitation in near-real-time sense is of high practical importance, as the quantitative results of this procedure may provide useful information to be used for the efficient planning of seismic protection measures. Furthermore, it may provide indications on the future evolution of this sequence, which is extremely important for both the public and authorities. A software package consisting of a number of sub-programs has been developed for this task. The main goal of this software is to obtain a semi -automatic evaluation of the possible evolution of a seismic excitation (sequence) already in progress. To achieve this target, successive determinations of basic parameters that characterize the sequence are performed and respective graphs are produced. In particular, the software automatically provides periodical snap-shots (within time periods defined by the user) describing how the shocks-members of the sequence are distributed in space, time, space-time and magnitude, allowing, this way, to detect possible variations in these parameters that could be connected to normal or non-normal evolution of the sequence. Application of this package has been performed during the recent seismic sequence which occurred SE of Lemnos island with a mainshock of M=5.9 (8/1/2013, 14:16 GMT). The snap-shots that described the evolution of the sequence and were produced by the application of the developed software package suggested a "normal" aftershock evolution during the first seven days of the main phase of this excitation.